2014
DOI: 10.1016/j.cogdev.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

What do different beliefs tell us? An examination of factual, opinion-based, and religious beliefs

Abstract: Children and adults differentiate statements of religious belief from statements of fact and opinion, but the basis of that differentiation remains unclear. Across three experiments, adults and 8-10-year-old children heard statements of factual, opinion-based, and religious belief. Adults and children judged that statements of factual belief revealed more about the world, statements of opinion revealed more about individuals, and statements of religious belief provided information about both. Children—unlike a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
58
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 38 publications
5
58
1
Order By: Relevance
“…Interestingly, the current findings differ from prior work comparing religious beliefs, factual beliefs, and opinions. In this prior work, children and adults distinguished among all three belief types when judging disagreements (Heiphetz et al, 2013;Heiphetz, Spelke, Harris, et al, 2014). The current findings indicate that such distinctions are limited to some domains (e.g., epistemology) and that individuals do not distinguish among these belief types along all dimensions.…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…Interestingly, the current findings differ from prior work comparing religious beliefs, factual beliefs, and opinions. In this prior work, children and adults distinguished among all three belief types when judging disagreements (Heiphetz et al, 2013;Heiphetz, Spelke, Harris, et al, 2014). The current findings indicate that such distinctions are limited to some domains (e.g., epistemology) and that individuals do not distinguish among these belief types along all dimensions.…”
Section: Discussioncontrasting
confidence: 40%
“…Children are more likely to report that only one person can be right in a disagreement concerning religious beliefs than in a disagreement concerning opinions (Heiphetz et al, 2013). Children also judge that religious beliefs reveal more information about the world than do opinions, whereas opinions reveal more information about individuals than do religious beliefs (Heiphetz, Spelke, Harris, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Kuhn, Zillmer, Crowell, and Zavala () found that social discussion on moral and philosophical dilemmas among adolescent peers could develop norms of argumentation, increasing the frequency of directive meta‐argumentation statements like “You need evidence for that claim” or “Tell us where you got that evidence.” They were also more likely to use evidence themselves than a control group from the same school who did not engage in such discussions (Kuhn & Moore, ). Related evidence shows that even young children are sensitive to differences between how different types of claims are discussed (Heiphetz, Spelke, Harris, & Banaji, ; Legare, Lane, & Evans, ; Woolley & Van Reet, ), suggesting that they may be attuned to the different ways in which these beliefs are justified as they are forming their own criteria for belief. In turn, this suggests that educational interventions could be successful at shaping how children evaluate different warrants for belief and how they learn to consider different sources of evidence ( cf .…”
Section: Discussionmentioning
confidence: 99%
“…Similar concepts are connected to norms, even though they are not explicitly included in the work of those authors who specifically studied social norms dynamics. Because they are a critical component of the grammar of society (Bicchieri, 2006), social norms are closely interwoven with other important processes (as the three we mentioned) and social and psychological concepts, such as attitudes (one’s individual preference about something; Petty & Brinol, 2010), factual beliefs (one’s beliefs about how the physical world functions; Heiphetz, Spelke, Harris, & Banaji, 2014), or self-efficacy and group efficacy (one’s beliefs about one’s or one’s group’s capacity to achieve a given goal; Bandura, Freeman, & Lightsey, 1999). These various constructs contribute to creating a web of meanings that affects how people feel, think, and act.…”
mentioning
confidence: 99%